Penerapan Model Course Review Horay untuk Meningkatkan Proses dan Hasil Belajar Siswa Kelas V - Yulia Yulia; Ritha Tuken; Husnul khatimah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the application of the Course Review Horay type cooperative learning model to improve the learning process about types of businesses in grade V students of SD Negeri 35 Sangtempe Enrekang Regency, and to determine that the application of the Course Review Horay type cooperative learning model can improve learning outcomes about types of businesses in grade V students of SD Negeri 35 Sangtempe Enrekang Regency. The approach used is a qualitative approach and the type of research used is class action research. The subjects of this study were fifth grade students of SD Negeri 35 Santempe, Enrekang Regency in the 2022/2023 school year totaling 12 people, consisting of 9 male students and 3 female students. Data collection techniques used in this study were observation, tests, and documentation. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. The research was conducted in two cycles. In cycle I the results of research on the learning process and learning outcomes were at sufficient qualifications. While in cycle II the results of this research on the learning process were in good qualifications with learning outcomes also in good qualifications.